Companion of the 18th Annual ACM SIGPLAN Conference on Object-Oriented Programming, Systems, Languages, and Applications - OOP 2003
DOI: 10.1145/949437.949440
|View full text |Cite
|
Sign up to set email alerts
|

Using AspectJ for component integration in middleware

Abstract: This report discusses experiences applying AspectJ [1] to modularize crosscutting concerns in a middleware product line at IBM®. Aspect oriented programming techniques were used to cleanly separate platform specific facilities for aspects such as error handling, performance monitoring and logging from base components, permitting those components to be reused in multiple environments. The initiative also guided the design of the AspectJ Development Tools (AJDT) for Eclipse, and influenced the technical directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…All authors come to the conclusion that AOP is a very promising approach, although still not widely used in the industrial practice [38]. In the middleware area several case studies showed that AOP allows software developers to scale features and footprint by supporting the static configuration of fine-grained configurable features [50,13,51]. All of these studies were conducted with AspectJ.…”
Section: Related Workmentioning
confidence: 99%
“…All authors come to the conclusion that AOP is a very promising approach, although still not widely used in the industrial practice [38]. In the middleware area several case studies showed that AOP allows software developers to scale features and footprint by supporting the static configuration of fine-grained configurable features [50,13,51]. All of these studies were conducted with AspectJ.…”
Section: Related Workmentioning
confidence: 99%
“…C4 uses AOP concepts to implement a "semantic patch system" for the application of kernel patches [16]. Several other publication show that AOP provides benefits for the development of configurable infrastructure software in the broad sense, namely middleware [8,31,19] and databases [29] product lines. All these studies demonstrate that there are real cases for aspects in system software.…”
Section: Applicationsmentioning
confidence: 99%
“…From the 28 analyzed kernel functions that are called directly or indirectly from the test applications and that are affected by interrupt synchronization, 19 functions turned out to be actually identically in the machine code 8 . Eight functions turned out to be minimal different with respect to the order of instructions and differences in sub-sequences of up to 4 instructions.…”
Section: Runtime Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Aspect Oriented Programming (AOP) has become an increasingly important software development method, whose goal is to improve the development and the maintenance of large applications through separation of concerns [6], [5], [3]. In AOP, a program is developed as a set of distinct, non-overlapping concerns, called aspects, Aspects are composed into a coherent application through a process called weaving, that takes place at various points of interest in the program-called join points.…”
Section: Introductionmentioning
confidence: 99%